The Oxford handbook of sovereign wealth funds - Cumming, Douglas,; Wood, Geoffrey E., 1945-; Filatotchev, Igor,; Reinecke, Juliane, (Oxford handbooks online., 2017)
Sovereign Wealth Funds have become increasingly powerful and influential investors. Their increasing role, and unusual character as both political and market actors, raise a number of issues with regard to finance, politics, regulation, and international business. This handbook draws together the growing but fragmented research on SWFs.